Chocolate covered murder ebook - Meier, Leslie (Lucy Stone, 2012)
It's frigid in snow-covered Tinker's Cove, and Lucy is fighting the winter blues—and her widening waistline. No one in their right mind would vacation in Maine this time of year, but to boost the economy, the town is launching a travel promotion for Valentine's Day. As a reporter for the Pennysaver, Lucy is assigned a puff piece on upscale Chanticleer's Chocolates, and its deliciously handsome owner, Trey Meacham. Soon Lucy discovers there's another tantalizing tart behind the counter. Sultry store manager Tamzin Graves is only too eager to serve her male customers. Leaving a throng of jealous women in her wake, it's almost no surprise when Tamzin turns up dead, her body covered in chocolate. . . Could a bitter ex-wife be behind the crimes? Or a candy shop competitor? There's no sugar-coating the truth, and as Lucy closes in on the culprit, she may find herself locked in the clutches of a half-baked killer. . . "I like Lucy Stone a lot, and so will readers." —Carolyn Hart "Fast-paced. . .intriguing." — Publishers Weekly "An enjoyable story." — RT Book Reviews